Membentuk Hukum bagi Perdamaian Aceh - Sulaiman Sulaiman (Universitas Syiah Kuala, 2012)
ABSTRACT: In social life, the law has many functions. In this case the law became a tool in resolving the conflict in Aceh. The conflict in Aceh has long occurred. Several rounds of dialogue has been conducted, but has not achieved satisfactory results. Dialogue after the tsunami last December 26, 2004, facilitated the Crisis Management Institute (CMI), the conflicting parties and the Government of the Free Aceh Movement reached a peace agreement. In peace, produced a memorandum of understanding (MoU) signed in Helsinki on August 15, 2005, in which the MoU is to be hold in drafting a legislation for Aceh, which was then named the Law Number 11 Year 2006 on the Government of Aceh. Legal Form for Aceh Peace